Can Virtually Trying on Apparel Help in Selecting the Correct Size?. (October 2019) - Hernández, Niina; Mattila, Heikki; Berglin, Lena
Close to 30% of garments bought online are returned, often due to issues of fit. These issues often relate to size selection, which is challenging without physically trying on a garment. Alternative methods need to be explored to select the best size in lieu of physically trying apparel on. To address this issue, we compare the size selections based on primary measurements and size charts, virtual garments, and real garments. A cross-sectional quantitative survey was carried out in an experimental setting. The participants (36, predominantly White females, aged 21–56) made size selections and evaluations based on virtual and real blouses and trousers. Selecting the size based on virtual garments is more accurate than size selection based on primary measurements and size charts, scoring 57% and 42%, respectively. Further research should be used to improve the virtual fitting room, with benefits such as fewer returns and more satisfied customers.